2012
DOI: 10.1175/2011jcli3934.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Land Surface and Atmospheric Initialization on Seasonal Forecasts with CCSM

Abstract: Series of forecast experiments for two seasons investigate the impact of specifying realistic initial states of the land in conjunction with the observed states of the ocean and atmosphere while using the National Center for Atmospheric Research (NCAR) Community Climate System Model, version 3 (CCSM3.0). Since direct soil moisture observations adequate for initialization of the land surface do not exist, this study considers proxy data. The authors are able to successfully initialize all components of the CCSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…It also can be speculated that the predictability source of the wet anomalies in the northern WUS in P2 is the combination of the low-frequency atmospheric internal variability and the tropical El Niño teleconnection. It has previously been reported that there is little evidence of an improved forecast of precipitation over land due to initialization of the atmosphere/land (Paolino et al 2012). However, this work shows that appropriate initialization of the atmosphere/land in addition to the ocean could substantially improve seasonal precipitation prediction.…”
Section: Conclusion and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It also can be speculated that the predictability source of the wet anomalies in the northern WUS in P2 is the combination of the low-frequency atmospheric internal variability and the tropical El Niño teleconnection. It has previously been reported that there is little evidence of an improved forecast of precipitation over land due to initialization of the atmosphere/land (Paolino et al 2012). However, this work shows that appropriate initialization of the atmosphere/land in addition to the ocean could substantially improve seasonal precipitation prediction.…”
Section: Conclusion and Discussionmentioning
confidence: 67%
“…Nevertheless, skillful seasonal prediction arising from the atmospheric state has been shown in some cases of summer heat waves and winter Arctic Oscillation for a one-season horizon (e.g., Jia et al 2016Jia et al , 2017. At shorter timescales, the influence of land initial conditions can be felt for weeks to months (Koster et al 2004(Koster et al , 2011Guo et al 2012;Paolino et al 2012). The intraseasonal low-frequency atmospheric oscillations with periods of 20-70 days (Ghil and Mo 1991;Plaut and Vautard 1994;Marcus et al 1994) can also modulate short-term seasonal climate prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Testing this hypothesis is one of the objectives of this study. While the impact of initialization of land and atmosphere on seasonal temperature and precipitation predictions has been previously explored in the literature (Paolino et al 2012;Koster and Suarez 2003), this study focuses instead on the impact of the increased resolution of land and atmosphere components on seasonal predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering and seminal works of Shukla and Mintz (1982) and Fennessy and Shukla (1999), a number of studies have explored the potential of soil moisture for seasonal climate predictability (e.g., Koster et al 2004;Ferranti and Viterbo 2006;Douville 2010;Paolino et al 2012;Materia et al 2014). The results indicate that moisture anomalies in the soil may persist for months, determining a land surface memory, which in some areas contributes to an increase in the seasonal predictability (Douville 2010;Paolino et al 2012;Materia et al 2014).…”
Section: Issues Of Predictability Predictions and Projectionsmentioning
confidence: 99%